THE PLACE OF PRIMARY NOMINATIONS IN THE CLASSIFICATION OF REPEATED NOMINATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the selection and interrelation of nominees of different systems in French and Uzbek, as well as the role of primary nominations in the classification of repeated nominations.